Analysis of Customer Satisfaction Level on International Departure Terminal Waiting Room Facilities at Sultan Syarif Kasim II International Airport - Chai runnisa (Politeknik Negeri Bengkalis, 2021)
The waiting room facilities service is very important to increase comfort and increase customer satisfaction. Improving services in terms of waiting room facilities needs to be done from time to time because the dynamic nature of customers and because of any customer tendency that wants to get something more and different. The research objective that wants to be achieved in this study is to know how the international departure terminal waiting room facilities at Sultan Syarif Kasim II International Airport influence on the customer satisfaction level. In this study, the population of the research is the users of the Sultan Syarif Kasim II International Airport flight services, especially the international departure terminal. The obtained research result has shown that the formulated hypothesis in proven that the international departure terminal waiting room facilities at Sultan Syarif Kasim II International Airport have a positive and significant influence on the customer satisfaction level.